Mapping of Flood-Prone and Dengue Fever-Prone Areas in Tahtul Yaman Village, Pelayangan District, Jambi City - Rini, Willia Novita Eka; Ranti, Andewi Amy; Putri, Najhoa Sonia; Situmorang, Muhammad Farhan; Salsabila, Mutiara; Marlina, Yeni; Permata, Cici; Meidita, Windi; Abyan, M. Gusman Syahlun; Firdaus, A. Somad; Al' Fajr (International Journal of Natural and Health Sciences, 2024)
Floods are natural events that come suddenly with an uncertain periodicity, except for areas that often experience annual flooding, such as in Tahtul Yemen Village. This flood disaster can cause health problems that threaten society, one of which is the Dangue Hemorrhagic Fever (DHF) outbreak. This activity aims to carry out mapping of flood-prone areas and dengue-prone areas in Tahtul Yemen Village to provide education about the management and prevention of dengue fever in order to improve the health status of the community, especially those in vulnerable areas. This research is exploratory research with an ecological study research design using Geographic Information Systems (GIS). Based on data on flood-prone areas obtained from 12 RTs in Tahtul Yaman Village, 5 RTs had a high percentage of being affected by flooding, 4 RTs had a moderate percentage of being affected by flooding, and 3 RTs had a low percentage of being affected by flooding. Meanwhile, for dengue-prone areas, there are 7 RTs with a low percentage, 3 RTs with a medium percentage, and 2 RTs with a high percentage. In conclusion, it was found that in Tahtul Yaman Subdistrict areas prone to flooding with the highest dominance are in RT 11,12,5,9, and 7 and areas prone to Dengue Hemorrhagic Fever (DHF) are dominant in RT 7 and 9. It is recommended that the areas that have been mapped be included in prone to flooding and Dengue Hemorrhagic Fever (DHF) strengthen drainage systems, green infrastructure, and increase public awareness about disease prevention